Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction